Siremis: Sistem Informasi Rekam Medis Puskesmas Kecamatan Matraman Jakarta - Helling, Lydia Salvina; Wahyudi, Endang; Hasanudin, Hasanudin (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2019)
The Matraman Sub-district Health Center, which was established on July 3, 1977 in DKI Jakarta, is one of the puskesmas that always records and searches its patient data in Medical Records. This Puskesmas requires a Medical Record Information System so that the recording of the patient's medical history can be stored and arranged in a good mechanism. The development of the patient data collection system in Medical Records uses the Waterfall method in developing the software. While the process of collecting data by conducting interviews with the relevant parts. Depictions of the running system can be seen in the form of Activity Diagrams and proposed systems can be seen in the Use Case Diagram, ERD and LRS. Research produces a Medical Record Information System that helps related parts in recording and searching for patient data needed quickly and precisely so that medical action can be done immediately.